Agricultural Production Assets Transfer and Poverty Upward Mobility in Isolated Areas of Zambia: A Domestic Life Cycle Perspective - Muyunda , Martin W (Asian Journal of Agriculture and Rural Development, 2013)
In Zambia poverty mitigation programmes based on agricultural production assets transfer constitute social protection and have been implemented to help the poor change their experiences of poverty and transform their social economic relationships. The effect of these programmes in realizing substantial poverty upward mobility has however been hindered by a myriad of factors including failure to understand the poor’s poverty situation and consequently misdirecting the poverty interventions. This study aims at clarifying changes in experiences of poverty due to agricultural production assets transfer, and identify potential intrinsic household attributes that could influence effective agricultural assets utilization among households within domestic life cycle stages. Participatory poverty profiling and rapid appraisals were done to respectively identify poverty perceptions and experiences, and elicit household attributes perceived to influence effective asset utilization. Data was collected from 150 randomly selected households. Results indicate that agricultural production assets transfer to poor rural households can help mitigate their poverty, but movement out of poverty does not spontaneously cover all poverty dimensions, and could be affected by intrinsic attributes of a household. Thus, anti-poverty programmes should pay enough attention not only to community age stratification but also to intrinsic household attributes and basic need areas which may respond most to interventions among the domestic life cycle stages.